Development Of Smartphone-Based Pornography Addiction Behavior Monitoring Application - Litafira Syahadiyanti; Alhifny Wahid; Bondan Tiur Mahendra (Sinkron : jurnal dan penelitian teknik informatika, 2026)
The rapid growth of smartphone usage has increased access to various internet content, including pornography-related websites, particularly among adolescents. Existing solutions addressing this issue generally focus on psychological screening or access restriction through parental control systems, which either rely on subjective input or emphasize blocking mechanisms rather than providing insights into actual usage behavior. This study aims to develop MindSafe, a smartphone-based application for monitoring pornography-related domain access activity using a local VPN approach. The proposed system captures domain access activity in real time by intercepting DNS queries at the device level, classifies accessed domains using a blocklist-based approach, and records the results in a structured database. Unlike conventional parental control systems that focus on access restriction, this study introduces a monitoring-oriented approach that emphasizes real-time domain logging and statistical behavior visualization. The system was developed using Agile methodology and evaluated through functional testing and usability assessment. Functional testing confirms that all core features operate as expected. Usability evaluation using the System Usability Scale (SUS) involving 20 respondents resulted in an average score of 76.0, indicating acceptable usability. The results demonstrate that the system provides an objective and privacy-aware monitoring approach, offering a data-driven alternative to existing screening and blocking-based solutions.